Salbutamol for analgesia in renal colic: study protocol for a prospective, randomised, placebo-controlled phase II trial (SARC) - Graham Johnson; Andrew Tabner; Apostolos Fakis; Rachelle Sherman; Victoria Chester; Elizabeth Bedford; Richard Jackson; Hari Ratan; Suzanne Mason (Trials, 2022)
Abstract Background Renal colic is the pain experienced by a patient when a renal calculus (kidney stone) causes partial or complete obstruction of part of the renal outflow tract. The standard analgesic regimes for renal colic are often ineffective; in some studies, less than half of patients achieve complete pain relief, and a large proportion of patients require rescue analgesia within 4 h. Current analgesic regimes are also associated with significant side effects including nausea, vomiting, drowsiness and respiratory depression. It has been hypothesised that beta adrenoreceptor agonists, such as salbutamol, may reduce the pain of renal colic. They have been shown to impact a number of factors that target the physiological causes of pain in renal colic (ureteric spasm and increased peristalsis, increased pressure at the renal pelvis and prostaglandin release with inflammation). There is biological plausibility and a body of evidence sufficient to suggest that this novel treatment for the pain of renal colic should be taken to a phase II clinical trial. The aim of this trial is to test whether salbutamol is an efficacious analgesic adjunct when added to the standard analgesic regime for patients presenting to the ED with subsequently confirmed renal colic. Methods A phase II, randomised, placebo-controlled trial will be performed in an acute NHS Trust in the East Midlands. Patients presenting to the emergency department with pain requiring IV analgesia and working diagnosis of renal colic will be randomised to receive standard analgesia ± a single intravenous injection of Salbutamol. Secondary study objectives will explore the feasibility of conducting a larger, phase III trial. Discussion The trial will provide important information about the efficacy of salbutamol as an analgesic adjunct in renal colic. It will also guide the development of a definitive phase III trial to test the cost and clinical effectiveness of salbutamol as an analgesic adjunct in renal colic. Salbutamol benefits from widespread use across the health service for multiple indications, extensive staff familiarity and a good side effect profile; therefore, its potential use for pain relief may have significant benefits for patient care. Trial registration ISRCTN Registry ISRCTN14552440 . Registered on 22 July 2019